Clinical Features and Symptom Recovery on a Gluten-Free Diet in Canadian Adults with Celiac Disease - Olga Pulido; Marion Zarkadas; Sheila Dubois; Krista MacIsaac; Isabelle Cantin; Sébastien La Vieille; Samuel Godefroy; Mohsin Rashid (Canadian Journal of Gastroenterology)
BACKGROUND: Celiac disease can present with mild or nongastrointestinal symptoms, and may escape timely recognition. The treatment of celiac disease involves a gluten-free diet, which is complex and challenging.